A Semiotic Analysis On “Covid-19 Vaccine: Bringing Us Together” Youtube Video - Dwi Pebrina Sinaga (INFOKUM, 2022)
This research is an analysis of non-verbal semiotic symbol found in a youtube video entitled “Covid-19 Vaccines: Bringing Us Together”. This research is to find out the kinds of signs dominantly found in “Covid-19 Vaccines: Bringing Us Together” video and how the meanings of the signs are realized in “Covid-19 Vaccines: Bringing Us Together” video. To answer the problem, the researcher used the theories of semiotics proposed by Peirce (1965) supported by Danesi (2010) and Wierzbicka (1996). The kinds of sign were analysed by the triadic semiotic theory of Peirce, the meaning of signs were analysed by the non-verbal theory of Danesi and the color meaning was analysed by color theory of Wierzbicka. The research method is descriptive qualitative approach. It is descriptive qualitative because the researcher used interpretive analysis to analyse the sign on covid-19 video. Interpretation in qualitative research is a symbolic interaction between researchers and human experiences, objects, people, situations, and events. The researcher found that there are 24 data that have signs related to covid-19. The kinds of signs appeared in “Covid-19 Vaccines: Bringing Us Together” video are icon, qualisign, symbol, sinsign, rheme, argument, and legisign. Icon occured the most of all with 11 occurences, followed by qualisign with 10 occurences, symbol with 8 occurences, signsign, rheme, and argument with 4 occurences for each, and the last is legisign with 2 occurences. On the other hand, there are 2 kinds of sign cannot be found in this data which are decisign and index.